Kanoniczne aspekty płci i transseksualizmu - Brzeziński, Maciej (Ius Matrimoniale, 2014)
Feminine and masculine are the fundamental and original human traits. Church claims that the sex is given at the moment of birth. Citation of the Holy Bible which describe sexuality almost always use biological criteria. On a field of canon law, sex changing issues and following consequences are forcing the Church to consider about possibilities of moderation of sex given at the moment of birth. Transsexualism is considered by a Church as a mental disease. Adapt surgery change just the external appearance but genetic structure remains the same. In terms of canon law the impossibility of primary sexual characteristics change makes surgeries uneffective. There is no possibility of sex change in the Baptist Certificate. The ability of concluding the valid marriage by a transsexual people is an interesting issue from the canon law point of view. Depending on the situation they cannot be married because of different obstacles: the same sex of nupturiens, impotence – can.1084, inability to take the essential obligations of marriage can. 1095 n.3.